2021
DOI: 10.1016/j.heliyon.2021.e06604
|View full text |Cite
|
Sign up to set email alerts
|

Micro-nano particulate compositions of Hypericum perforatum L in ultra high diluted succussed solution medicinal products

Abstract: The fact that many patients all over the world use homeopathic ultra high diluted succussed medicinal products, makes very interesting an explanation about the structure of them since until now only unconfirmed hypotheses are made. The present study focuses on the still unanswered questions about what happens with the chemical composition and the physicochemical properties of these products using Hypericum Perforatum L as a representative paradigm. All samples were prepared according to manufacturing procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…66 Using probing tools of nanoscience, many independent research groups confirmed that nanoparticles are present in ultra-high dilutions used as medicines in homeopathy. [23][24][25][26][27]67,68 The vigorous shaking process used in homeopathy increases the water pressure in the glass bottle substantially. A lot of bubbles and nanobubbles are formed.…”
Section: How Ultra-high Dilutions May Work As Nanomedicinesmentioning
confidence: 99%
“…66 Using probing tools of nanoscience, many independent research groups confirmed that nanoparticles are present in ultra-high dilutions used as medicines in homeopathy. [23][24][25][26][27]67,68 The vigorous shaking process used in homeopathy increases the water pressure in the glass bottle substantially. A lot of bubbles and nanobubbles are formed.…”
Section: How Ultra-high Dilutions May Work As Nanomedicinesmentioning
confidence: 99%
“…Moreover, it was revealed that these solutions are self-organized dispersed systems in which nano-objects are formed [4]. It was also observed that the ingredient trituration process in lactose powder is accompanied by the formation of micro-and nano-particulates [2]. Their biological activity and mechanism of action were previously established [5], and insights into the molecular mechanism of their action were gained [6].…”
Section: Introductionmentioning
confidence: 99%
“…Also, lactose is a commonly used component of pharmaceutical medications in tablet form. The structure of lactose triturated with an active pharmaceutical ingredient differs from the pure crystalline lactose; it is due to the destruction and creation of new chemical groups in lactose and modification of its crystal structure [2]. In [3], lactose conformation was changed by saturation in fluidized beds with active pharmaceutical ingredients obtained by repeated dilution of antibodies (Abs) to interferon-gamma (IFN-γ) in combination with an external intensive vibration treatment between the dilution steps.…”
Section: Introductionmentioning
confidence: 99%
“…These nanoparticles, which can be used in medical device coatings, antibacterial products, cosmetics, food, and pharmacy, can also be employed both as medicine and as drug carrier thanks to their unique physical and chemical properties (86,149). Utilization of H. perforatum in nanoparticular carrier systems was investigated in many studies (150)(151)(152).…”
Section: Medicinal Usesmentioning
confidence: 99%